2017
DOI: 10.1093/ntr/ntx099
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Smokers in the United States: 2008–2014

Abstract: The greater prevalence and increasing rate of Serious Psychological Distress among smokers, relative to former- and never-smokers, from 2008 to 2014 provides support that the greater mental health burden among smokers may be contributing to the slowed reduction in smoking prevalence in the United States. In addition, relationships between SPD and smoking were consistently stronger among smokers with higher levels of education and annual family income. Such results suggest the necessity of incorporating mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Although the “hardening hypothesis” has received mixed support, especially in terms of observed increases in nicotine dependence among smokers over time, 5559 our findings are not incongruous with the basic premise of this hypothesis, which is to suggest that today’s remaining smokers may have more trouble quitting because of an increasing preponderance of potential barriers to smoking. Specifically, we found that use of some illicit drugs is increasing among smokers, adding to other recent findings of increases in depression, 33 severe psychological distress, 34 and anxiety 35 among cigarette smokers. Yet, we also found that the rate of increase in drug use is most rapid among former smokers.…”
Section: Discussionsupporting
confidence: 79%
“…Although the “hardening hypothesis” has received mixed support, especially in terms of observed increases in nicotine dependence among smokers over time, 5559 our findings are not incongruous with the basic premise of this hypothesis, which is to suggest that today’s remaining smokers may have more trouble quitting because of an increasing preponderance of potential barriers to smoking. Specifically, we found that use of some illicit drugs is increasing among smokers, adding to other recent findings of increases in depression, 33 severe psychological distress, 34 and anxiety 35 among cigarette smokers. Yet, we also found that the rate of increase in drug use is most rapid among former smokers.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to perceived stress, psychological distress has been associated with higher smoking prevalence, nicotine dependence, and lower rates of cessation (7). In the U.S., the rates of smoking among individuals with high self-reported non-specific psychological distress in the last 30 days were over 30% in 2014 which were more than double the rates for individuals with no psychological distress (8, 9). Higher psychological distress is associated with greater overall nicotine dependence, including shorter time to the first cigarette of the day and stronger smoking urges (7).…”
Section: Introductionmentioning
confidence: 99%
“…Our results went in line with Choi et al’s study, who experimentally found that smoking might relieve physiological and psychological responses to stress (Choi, Ota, & Watanuki, ). On the other hand, several studies reported that smoking was positively associated with PD (Choi, Chan, & Lehto, ; Zvolensky et al, ). Skov‐Ettrup, Nordestgaard, Petersen, and Tolstrup () concluded from a large study (including 90,108 participants) that there was no clear evidence that high tobacco smoking was causally associated with PD, but co‐occurrence is important to be considered in interventions for smoking cessation, whatever causes this strong association.…”
Section: Discussionmentioning
confidence: 99%
“…According to Boksa, smoking acts as (a) a causal factor of some mental disorders, (b) a factor modulating presentations of mental disorders, and (c) as a factor modulating progression and medications of mental disorders (Boksa, 2017 the other hand, several studies reported that smoking was positively associated with PD (Choi, Chan, & Lehto, 2018;Zvolensky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%